2001
DOI: 10.1016/s0092-8674(01)00342-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Kir2.1 Cause the Developmental and Episodic Electrical Phenotypes of Andersen's Syndrome

Abstract: Andersen's syndrome is characterized by periodic paralysis, cardiac arrhythmias, and dysmorphic features. We have mapped an Andersen's locus to chromosome 17q23 near the inward rectifying potassium channel gene KCNJ2. A missense mutation in KCNJ2 (encoding D71V) was identified in the linked family. Eight additional mutations were identified in unrelated patients. Expression of two of these mutations in Xenopus oocytes revealed loss of function and a dominant negative effect in Kir2.1 current as assayed by volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
731
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(754 citation statements)
references
References 43 publications
13
731
1
9
Order By: Relevance
“…As mentioned earlier, the deletion of patient 4 includes KCNJ2 of which heterozygous mutations are causal for Andersen syndrome. 37 This syndrome is characterized by periodic paralysis, ventricular arrhythmias and prolonged QT intervals, dental anomalies, small hands and feet, low-set ears, hypertelorism, micrognathia, fifth-digit clinodactyly and syndactyly. Also, joint laxity has been reported.…”
Section: Cardiac Malformationsmentioning
confidence: 99%
“…As mentioned earlier, the deletion of patient 4 includes KCNJ2 of which heterozygous mutations are causal for Andersen syndrome. 37 This syndrome is characterized by periodic paralysis, ventricular arrhythmias and prolonged QT intervals, dental anomalies, small hands and feet, low-set ears, hypertelorism, micrognathia, fifth-digit clinodactyly and syndactyly. Also, joint laxity has been reported.…”
Section: Cardiac Malformationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] This skeletal muscle syndrome is associated with periodic paralysis often linked to fluctuations in plasma potassium levels. 2,7,8 Clinical studies indicate that Andersen-Tawil syndrome may be associated with arrhythmias, particularly when aggravated by other health problems such as infection.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that pausedependence of TdP is predominant in LQT2 patient and rare in LQT1 and LQT3 (Tan et al, 2006). Similarly, exercise or mental stress has been reported to be a trigger for ventricular arrhythmias in LQT4 patients (Mohler et al, 2003) and hypokalemia is often associated with frequent ventricular arrhythmia in LQT7 (Plaster et al, 2001). Information on genotypespecific triggers can enable physicians to take patient-tailored approach in recommending physical and sports related activities and avoiding specific triggers in LQTS patients.…”
Section: Genotype Specific Triggers Of Arrhythmic Events-thoughmentioning
confidence: 99%
“…The newer more detailed classification scheme is based on the genetic mutation involved. Ten forms of congenital LQTS have been identified due to mutations in genes encoding for potassium channels, sodium channels or membrane components located on chromosome 3, 4, 6, 7, 11, 17 and 21 (Table 1) (Andersen et al, 1971;Tawil et al, 1994;Splawski et al, 2000;Plaster et al, 2001;Mohler et al, 2003;Splawski et al, 2004;Vatta et al, 2006;Medeiros-Domingo et al, 2007).…”
Section: Molecular Genetics Of Lqtsmentioning
confidence: 99%
See 1 more Smart Citation